2013
DOI: 10.1111/are.12193
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus (WSSV) prevalence associated with disease resistance among wild populations of black tiger shrimp,Penaeus monodon(Fabricius)

Abstract: White spot disease caused by white spot syndrome virus (WSSV) is the major issue of huge economic destruction globally in the shrimp aquaculture industry. In the present investigation, WSSV prevalence associated with disease resistance was studied among wild black tiger shrimp, Penaeus monodon (Fabricius) from four distant geographic locations along the East coast of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Dutta et al . () reported the usefulness of real‐time PCR for the detection of WSSV at low viral load and also predicted the possibility of detection of WSSV infection at initial stage and could take immediate preventive measure of WSSV in cultured shrimp. Therefore, real‐time PCR may be used to detect WSSV‐infected PL of shrimp before stocking to the farm.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Dutta et al . () reported the usefulness of real‐time PCR for the detection of WSSV at low viral load and also predicted the possibility of detection of WSSV infection at initial stage and could take immediate preventive measure of WSSV in cultured shrimp. Therefore, real‐time PCR may be used to detect WSSV‐infected PL of shrimp before stocking to the farm.…”
Section: Resultsmentioning
confidence: 96%
“…The gross clinical sign of this disease is the appearance of white spots on cuticle, and as a result, rapid reduction in food consumption and abnormal movement appear (Dutta et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, for the first time in P. monodon , a 71 bp microsatellite DNA marker was reported to be significantly present in disease‐susceptible shrimps (Mukherjee and Mandal, ). Later on, WSSV challenge experiment also showed that 1.21 × 10 3 fold higher WSSV propagation occurred in disease‐susceptible shrimps establishing the significant link between this marker and disease susceptibility (Dutta et al., ). Additionally, a 457 bp DNA marker developed by RAPD‐SCAR method was also found in P. monodon , which is mostly present in the disease‐resistant shrimp.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of WSSV has been reported widely among wild and cultured shrimp. It has been reported that the WSSV prevalence in wild Penaeus monodon was high (56.2%) in Chennai, Tamil Nadu followed by Digha, West Bengal (10.9%), and Visakhapatnam, Andhra Pradesh (0.6%) in India (Dutta et al, 2013). In another study, the prevalence of WSSV was reported to be only about 3.6% in wild invertebrates such as crabs, blue, white and brown shrimps and vertebrates in the environment surrounding shrimp farms along the Pacific coast of Mexico (Macías-Rodríguez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%